The long‐term impact of receiving incidental findings on parents undergoing genome‐wide sequencing. Issue 4 (6th February 2022) - Cheung, Faith; Birch, Patricia; Friedman, J. M.; ,; ,; Elliott, Alison M; Adam, Shelin
Abstract: Genome‐wide (exome or genome) sequencing (GWS) has the potential to detect incidental findings (IFs): variants unrelated to the primary indication for testing that may be of medical or personal utility. As GWS becomes increasingly common in clinical practice, it is important to understand the impact of IFs on the individuals and their families. Our goal was to explore the immediate and long‐term lived experience of individuals who received IFs as part of diagnostic GWS. We interviewed parents who received an IF as part of the CAUSES translational research study at Children's and Women's Health Centre of British Columbia. Five hundred families were offered trio‐based GWS for their child with a suspected, undiagnosed genetic condition. Nine hundred and one of the 1000 parents chose to find out about IFs and 21 parents received an IF for themselves. Twelve of these parents participated in this study. They were interviewed an average of 2.3 years after the IFs were returned. Thematic analysis of transcribed interviews revealed that the participants' decisions and motivations to receive IFs were influenced by personal values and beliefs and by having a child with a suspected genetic condition. Participants' experiences were also influenced by the type of IF received, having a personal or family history of a related condition, their personal interpretation and perceived utility of the information, and the impact of the IF on other family members. Participants expressed either no regret or mild decisional regret on the Decisional Regret Scale. Two years post results, most participants reported little negative impact from receiving the IF. The utility of the information varied: some reported lifestyle changes and proactive screening, while others felt the information may be more relevant in the future. Understanding the immediate and longer term impact of receiving IFs from GWS can inform both pre‐ and post‐test genetic counseling.